The impact of residency training in family medicine in promoting the attributes of primary care in Rio de Janeiro - Jantsch, Adelson Guaraci (2020)
For the last 40 years, several improvements in Primary Health Care (PHC) were made worldwide due to the momentum created by the Alma-Ata declaration. Many countries have achieved good results in creating and developing universal PHC systems and today enough evidence supports the notion that countries with strong PHC have better health indicators, have reduced health inequalities, and get better results while spending less money. In the last 25 years, Brazil has experienced a unique moment in its history. With the creation of the Family Health Strategy in 1994, there was a great expansion of the primary care services a marked growth in new Family Medicine residency programs. In March 2012, the Rio de Janeiro Municipal Health Department (RJ-MHD) created a new Family Medicine (FM) residency program as an initiative for capacity building of human resources in health care and quality improvement of the medical workforce. The rationale behind the creation of this FM Residency Program (RJ-FMRP) was based on the policymakers’ assessment that the quality of care provided by physicians without residency training in FM (RTFM) in the new clinics was below the desired standard, was inefficient and had a narrow scope of medical actions. RTFM was considered by policymakers at the RJ-MHD as the gold-standard of medical education and FM the medical specialty to provide community-based PC. The main objective of this study is to measure the impact of the RJ-FMRP in promoting the attributes of primary care in Rio de Janeiro. A database was created combining information from 949.957 patients’ electronic health records, 429.189 referrals to secondary care, 151.110 hospital admissions and 15.829 deaths registries. Observational retrospective studies of 5 363 407 consultations in primary care were performed comparing doctors without residency training in FM (Generalists) and trained family physicians. Six articles were produced presenting the justification for this project, the construction of the database, the intervention (RJ-FMRP) and empirical studies showing that RTFM enables FPs to be more competent to diagnose a wide range of chronic diseases while requiring fewer laboratory tests and requesting fewer referrals to secondary care for ambulatory care of health conditions. On the other hand, RTFM makes doctors request more often referrals for surgical treatment for their patients, such as cataract surgery. RTFM also prevents a series of hospital admission from happening, within the universe of ambulatory-care sensitive conditions, but also in an expanded universe of conditions, which includes mental health conditions, while increasing the demand for hospital admission in conditions such as cardiac arrhythmias, pacemaker implantation, and AIDS/HIV treatment. Finally, all of these events happen in a more coordinated way between the levels of care, but also over time, since trained FPs promote more follow-up consultations with their patients, either after diagnosing a chronic condition, after referring a patient to secondary care or, in most cases, after a hospital stay